Medical Oncology Group of Australia position statement and membership survey on voluntary assisted dying. Issue 7 (8th July 2018) - Karapetis, Christos S.; Stein, Brian; Koczwara, Bogda; Harrup, Rosemary; Milleshkin, Linda; Parente, Phil; Millward, Michael; Haines, Ian; Blinman, Prunella; Olver, Ian
Abstract: The controversial topic of voluntary assisted dying (VAD) is receiving significant attention at state government levels and in the community. Acknowledging potential legalisation of VAD, the Medical Oncology Group of Australia (MOGA) undertook a survey of members to inform the development of a position statement on the subject. All MOGA members were invited to complete an anonymous online survey. The survey comprised 12 closed‐response categorical questions. Descriptive statistics were used to summarise the survey data. Majority views expressed in the survey would form the basis of a MOGA position statement on VAD. A total of 362 members completed the questionnaire, representing 55% of the membership; 47% of respondents disagreed with VAD; 36% agreed with VAD and the remaining members (17%) were 'neutral'. A clear majority position was not established. Only 14% agreed that physicians involved in VAD should be required personally to administer the lethal medication; 94% supported conscientious objection of physicians to the VAD process; 95% agreed that a palliative care physician consultation should be required and 86% agreed with the need for the involvement of specialist psychiatry medical services before a patient can be deemed as suitable for VAD. The MOGA membership expressed a range of views on the topic of VAD. A clear majority‐held view to support a MOGA position that either supports or opposes VAD was not established. The position statement that flows from the survey encourages informed debate on this topic and brings into focus important considerations.